Paraproteinemia associated Peripheral Neuropathy - Rajbhandary, Sajin (Nepalese Journal of Cancer, 2017)
Peripheral Neuropathy can be acute or gradual over the years turning severe and quite debilitating to the patient. Diabetes, Alcohol or Drugs are some of the common causes of neuropathies however a small percentage of patients can present with paraproteinemia. The cause of paraproteinemia in these patients range from benign to serious malignant disorders such as Multiple Myeloma. We here report a case of an elderly patient who had to visit multiple center for over 4 months for his chronic neuropathy. Following extensive workup, he was started on an immunomodulating agent and glucocorticoids. Patient has remained free of disease and symptom free throughout treatment and thereafter.